Analysis of the molecular interactions governing the polymorphism of benzamide – a guide to syntheses? - Ectors, Philipp; Zahn, Dirk (Physical Chemistry Chemical Physics, 2013)
Dispersion-corrected density functional calculations are used to rationalize the subtle differences in the molecular interactions in benzamide crystals. The potential energy of the different polymorph structures is dominated by the interplay between intermolecular attraction and molecular torsion/deformation to accommodate favourable molecular packing. Using suitable proxies arranged in pseudo-crystalline setups we discriminate the contribution of hydrogen bonding, extgreekp– extgreekp interactions and intra-molecular interactions to the lattice energies of the most relevant (P1 and P3) benzamide polymorphs. Strikingly, these commonly anticipated binding/packing concepts cannot account for the observed ranking of benzamide structures, thus hinting at the importance of the interactions between the benzene rings and the polar amide groups. Moreover, individual structural motifs that account for the competition between the two crystal structure types are elaborated. On the basis of such in-depth understanding of molecular interactions – in terms of both structure and chemistry – we suggest nucleation scenarios as guides to a more controlled synthesis of the stable P1 form or to direct nucleation in favour of the P3 polymorph.
EAM Import::2019-03-13